Aster pseudoglehni extract stimulates cholecystokinin and serotonin secretion in vitro and reduces gastric emptying in vivo - Hye Young Kim; Kyong Kim; Yu Mi Lee; Hyunnho Cho (Journal of Functional Foods, 2017)
Aster pseudoglehni (Asteraceae) (AP) is a perennial plant from the Asteraceae family that is indigenous to Korea, and has traditionally been used as famine relief food in Korea. However, the effect of AP on food intake has not been characterized scientifically. The present study aimed to investigate the effect of the aqueous ethanolic extract of AP (AEE-AP) on food intake-related parameters in vitro and in vivo. AEE-AP stimulated cholecystokinin (CCK) secretion in enteroendocrine STC-1 cells, and serotonin (5-HT) secretion in RIN14B cells, an enteroendocrine cell model. Furthermore, AEE-AP affected physiological processes related to food intake in rats. Single oral administration of AEE-AP activated c-Fos in the dorsal vagal complex (DVC) and the arcuate nucleus of the hypothalamus (ARC), and delayed gastric emptying in rats. Our results demonstrated that AEE-AP regulated food intake-related parameters in the enteroendocrine system and gastrointestinal motility that affect food intake and eventually obesity.